A comparative investigation on temperature distribution in electric discharge machining process through analytical, numerical and experimental methods. (March 2017) - Fazli Shahri, Hamid Reza; Mahdavinejad, Ramezanali; Ashjaee, Mehdi; Abdullah, Amir
Abstract: Electric discharge machining (EDM) is a widely-used non-traditional machining process in manufacturing of complicated structures based on localized thermal loads. Because of numerous difficulties in measuring temperature, no adequate knowledge on temperature distribution of workpiece, tool and plasma channel is available. On one hand, a large number of dispersedly-published papers have been reported so far to model the temperature distribution either analytically or numerically. On the other hand, an enormous amount of experimental attempt has been put into measuring the temperature by directly-measuring methods. In this study, a comprehensive review of analytical, numerical and experimental investigations on temperature prediction has been provided to organize different methods to integrate them as useful information for elucidating the differences between approaches and identifying their proximities to the real temperature distribution. This review also prepares a classification of the different methods of investigating temperature and provides an overview of some of the recent advances in this area to help researchers on selecting appropriate approaches among analytical, numerical and experimental techniques depends on applications and the availabilities of those techniques. The assumptions, limitations and features of different methods are described. Finally, the paper shows some required enhancements for EDM process to improve the total accuracy of temperature prediction as well as recommendations for future studies. Highlights: The vast array of research works ranging from the analytical approaches of temperature distribution analysis to the numerical and experimental techniques are discussed. Useful information on limitations, features, assumptions and characteristics of theoreticalmodels of EDM process are provided. The numerical analysis researches are described in two separate models namely FEM and FDM. Two types of temperature measurement techniques namely thermocouple and optical emission spectroscopy technique are reviewed. This paper provides categorized information, recommendation, for further research to the temperature distribution.